Sea ice variability in the Nordic Seas over Dansgaard–Oeschger climate cycles during the last glacial – A biomarker approach - Sadatzki, Henrik (The University of Bergen, 2020)
Accessible after 2020-11-10 The Arctic sea ice cover is in fast transition. Resolving past sea ice fluctuations and its link with abrupt climate change might be key for a better understanding of yet unknown climatic consequences of future Arctic sea ice loss. The last glacial period was marked by recurring abrupt climate changes, referred to as Dansgaard–Oeschger (D–O) climate cycles. These D–O climate cycles and in particular the associated abrupt warming transitions by up to 15°C over Greenland happening within years or decades might have been linked to shifts in sea ice cover in the Nordic Seas. This PhD thesis aims at resolving and constraining the largely unknown millennialscale sea ice variability in the Nordic Seas and its pivotal role for abrupt climate changes during the D–O cycles based on empirical proxy data evidence. Novel sea ice reconstructions are mainly based on the sedimentary abundances of the sea ice algae biomarker IP25 and open-water phytoplankton biomarkers. This thesis includes two multi-decadal to centennial-scale biomarker sea ice records from the southern and central Norwegian Sea covering the time period ~30–40 thousand years ago, which reveal unprecedented insights into the nature of glacial sea ice fluctuations during D–O cycles (Papers 1 and 2). A comparison of these biomarker sea ice records with LOVECLIM model output data of sea ice cover (Paper 1) and a new bromine-enrichment sea ice record from the RECAP ice core (East Greenland) (Paper 2), sheds light on the mechanisms and timing of rapid sea ice shifts with respect to abrupt Greenland climate changes. A third biomarker sea ice record from the Eirik Drift south of Greenland elucidates the sea ice cover and export in the northwestern North Atlantic ~30–40 thousand years ago (Paper 3). This thesis also comprises a calibration based on a robust linear correlation between the sea ice index PIP25 in (sub-)Arctic surface sediments and modern spring sea ice concentration, which allows a quantification of past sea ice changes (Paper ...